2014
DOI: 10.1002/hbm.22504
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted network architecture of the resting brain in attention‐deficit/hyperactivity disorder

Abstract: Consistent with existing theoretical models, these results provide evidence that default network-ventral attention network interconnections are a key locus of dysfunction in ADHD. Moreover, these findings contribute to growing evidence that distributed dysconnectivity within and between large-scale networks is present in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
163
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 164 publications
(181 citation statements)
references
References 80 publications
15
163
1
2
Order By: Relevance
“…More specifically, decreased intrinsic segregation of the attention networks may alter the information exchange threshold between the two systems with VAN signals interrupting goal-directed task-relevant DAN activity. This is consistent with recent findings that increasingly point to VAN as the locus of attentional dyscontrol and enhanced distractibility in ADHD [27,61,62]. For instance, López et al [63] observed that in the ADHD group, but not in controls, unattended task-irrelevant distractors elicited increased VAN-related P300 activity.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…More specifically, decreased intrinsic segregation of the attention networks may alter the information exchange threshold between the two systems with VAN signals interrupting goal-directed task-relevant DAN activity. This is consistent with recent findings that increasingly point to VAN as the locus of attentional dyscontrol and enhanced distractibility in ADHD [27,61,62]. For instance, López et al [63] observed that in the ADHD group, but not in controls, unattended task-irrelevant distractors elicited increased VAN-related P300 activity.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, in the context of ADHD this might be hypothesized to relate to symptoms of distractibility and inability to ignore irrelevant stimuli. It is however difficult to directly compare our results with previous studies as a differentiation between the VAN and SN is often not made [62]. For instance, Sripada et al [62] did not differentiate between the VAN and SN and included insula as part of the VAN.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations